Proceedings 20th IEEE International Parallel &Amp; Distributed Processing Symposium 2006
DOI: 10.1109/ipdps.2006.1639358
|View full text |Cite
|
Sign up to set email alerts
|

Non-cooperative, semi-cooperative, and cooperative games-based grid resource allocation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Similarly to the example in Khan and Ahmad [32] discussed in Sect. 2.3 this is not self-interested behaviour.…”
Section: Decentralised Market Mechanismsmentioning
confidence: 79%
See 2 more Smart Citations
“…Similarly to the example in Khan and Ahmad [32] discussed in Sect. 2.3 this is not self-interested behaviour.…”
Section: Decentralised Market Mechanismsmentioning
confidence: 79%
“…Khan and Ahmad [32] show that in any cooperative approach, global optima can only be achieved when all the nodes cooperate. In a discussion of lessons learnt from experience with load management in giant-scale web services, Brewer [5] proposes the idea of incorporating, into a request for a resource, a notion of its value or cost.…”
Section: Existing Market-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schedulers have to take into account the network bandwidth availability and the latency of data transfer between a computational node to which a task is going to be submitted, and the storage resource(s) from which the data required is to be retrieved [19], [11]. Therefore, the scheduler needs to be aware of any replicas "close" to the computation node and if the replication is coupled to the scheduling, then create a new copy of the data.…”
Section: Data Grid Elementsmentioning
confidence: 99%
“…Khan [17] classified game-based co-allocation models into three types: cooperative, semi-cooperative and non-cooperative. By extensive simulations, they concluded that the cooperative method leads to better task rejection, utilization and turnaround time as well as comparable load fairness and makespan.…”
Section: Related Workmentioning
confidence: 99%